Pelatihan Pemanfaatan Teknologi Informasi Dan Internalisasi Nilai Pancasila Dalam Mendorong Ekonomi Kreatif Berbasis Potensi Lokal Di SMA Negeri 2 Bukittinggi - Elmi Rahmawati; Novalia Indra; Vivi Puspita Sari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The advancement of information technology in the digital era requires students to possess strong digital literacy skills and the ability to utilize them productively in their daily lives. Meanwhile, character education—through the internalization of Pancasila values—serves as a crucial aspect in shaping a young generation characterized by integrity, responsibility, and social awareness. As a secondary educational institution, SMA Negeri 2 Bukittinggi has significant potential for developing a creative economy based on local potential. However, initial observations indicate that students are not yet optimally utilizing information technology as a means of developing the creative economy, and that Pancasila values ​​have not yet been integrated into entrepreneurial practices. This community service activity aims to improve students' digital literacy, instill Pancasila values ​​in creative economic activities, and encourage the development of products based on local potential through the use of information technology. The methods used include outreach, training, hands-on practice, and mentoring. The expected outcomes are improved students' digital skills, the development of locally based creative economic products, and the development of civic character aligned with Pancasila values.